Pengaruh Roe Dan EPS Terhadap Harga Saham Pada Perusahaan Sub Sektor Rokok Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021 – 2023 - Eka Fitriatul Afifah; Monalisa (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to examine the effect of Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices in cigarette sub-sector companies listed on the Indonesia Stock Exchange in 2021-2023. This research method uses multiple linear regression analysis using the STATA 17 statistical test tool. The sampling method in this study used purposive sampling technique. The F test results show that ROE and EPS simultaneously affect the stock price. The T test results show that EPS partially affects the stock price.